Rare case of granular cell tumour at 16 years - A case report - S M Balaji; Preetha Balaji (Wolters Kluwer Medknow Publications, 2022)
Rationale: Granular cell tumours (GCTs) of the tongue are a rare, soft tissue pathological entity at young ages. This case report aims to present one such case. Patient Concerns: A 16-year-old female patient sought treatment for a small, slow-growing, painless nodule in the dorsum of the tongue since six months. She underwent successful orthodontic treatment in recent past and is in the retention phase. Diagnosis: Excisional biopsy revealed the lesion to be a GCT under histopathology. Treatment: The patient was treated for an abnormal, small, slow-growing, painless nodule in the dorsum of the tongue. Outcomes: The patient had satisfactory esthetics and early diagnosis. The active intervention dispelled the confusion about the role of trauma and orthodontics appliance in the etiology of GCT in this particular case to the patient. Take-away Lessons: GCT can occur at any age. Early diagnosis and corrective surgery would help to avoid late complications.